Limestones under salt decay tests: assessment of pore network-dependent durability predictors - Alves, Carlos (2011)
Three Portuguese limestones (two grainstones, Semi-rijo and Moca Creme commercial types, and a trav-ertine) were subjected to salt crystallisation test (EN 12370:1999). Grainstones specimens showed higher weight loss than the travertine ones. Results are discussed, using parametric and nonparametric statistics, in relation to pore space characteristics that have been considered durability predictors, evaluated at the macroscopic (water imbibition) and microscopic (mercury injection porosimetry) levels. Several of the pore-space parameters indicate differences between grainstones and travertine, but these differences are much lower than the differences in weight loss. Results of the durability dimensional estimator (DDE) seem to present a discrepancy, with higher values in the rock type having lower weight loss (travertine). Additionally, weathering patterns of travertine samples show marked irregularities (a feature that is not assessed by weight loss). These irregularities are attributed to heterogeneous spatial distribution of detritic components (a feature that is not assessed by pore-space parameters). Comparing the grain-stones, Moca Creme showed higher values of mass loss and several durability predictors suggested noteworthy differ-ences in relation to Semi-rijo. However, these differences are much lower than differences in weight loss. Calculated crystallisation pressures are even higher for Semi-rijo. It is proposed that petrographical aspects of Moca Creme, namely heterogeneity related to the presence of bioclasts and veinlets, could contribute to explain the higher weathering susceptibility of this rock type. These results highlight the need to include petrographical features in assessments of durability and the usefulness of visual description on the characterization of salt weathering.